2012
DOI: 10.1093/ndt/gfr772
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of renal arterial resistance index upon renal allograft survival: the time point matters

Abstract: In our hands, the RI obtained during the first 6 months after transplantation failed to predict renal allograft failure or death, whereas the RI measured 12-18 months after transplantation appeared useful to predict long-term allograft outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 11 publications
5
42
0
Order By: Relevance
“…For this reason, the measure of RRI in the late period of posttransplant follow-up, as it is the case in many patients of Radermarcher study, can give a major prognostic role. This point was stressed by the study of Kramann et al [37]: this author clearly showed that measure of RRI within 6 month after transplantation fail to predict renal allograft failure or death in patient with stable renal function (serum creatinine 1.7 ± 0.9 mg/dL) while measuring RRI later, 12-18 months after transplantation, is useful as a prognostic marker of long-term clinical outcomes (renal allograft failure or death), mainly when RRI [0.75.…”
Section: Rri and Renal Allograft Survivalmentioning
confidence: 97%
“…For this reason, the measure of RRI in the late period of posttransplant follow-up, as it is the case in many patients of Radermarcher study, can give a major prognostic role. This point was stressed by the study of Kramann et al [37]: this author clearly showed that measure of RRI within 6 month after transplantation fail to predict renal allograft failure or death in patient with stable renal function (serum creatinine 1.7 ± 0.9 mg/dL) while measuring RRI later, 12-18 months after transplantation, is useful as a prognostic marker of long-term clinical outcomes (renal allograft failure or death), mainly when RRI [0.75.…”
Section: Rri and Renal Allograft Survivalmentioning
confidence: 97%
“…from a deceased or living donor) is a crucial factor that could potentially confound studies attempting to define a prognostic role for the RI in kidney-graft recipients (19). This is because kidneys harvested from cadaveric donors usually undergo a substantially long period of cold ischemia that could affect the RI after transplantation (8). Although numerous studies have investigated the usefulness of Doppler US examination of the intrarenal arteries in renal transplant patients, to the best of our knowledge, the optimal artery for examination has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…They assessed the RI performed 1 day after transplantation in 343 patients and found that graft survival was significantly lower in patients with RI greater than 0.70. Recently, Kramann et al 29 showed that the RI obtained within 6 months after transplantation failed to predict graft survival, whereas the 12-to 18-month posttransplant RI was significant predictor.…”
Section: Discussionmentioning
confidence: 99%